Cerebral artery resistive index in preterm infants and impact of patent ductus arteriosus - Moonisah Rafiq; Aamir Rashid; Javid Iqbal; Sheikh Riyaz; Feroz Shaheen; Mushtaq Bhat; Jan Mohd Sheikh; Yahya R. Bhat; Zubair Mushtaq Tramboo (Heart India)
Introduction: There is a lack of reference values for the resistive index (RI) of cerebral arteries in preterm infants for our local population. There is a lack of data on the impact of patent ductus arteriosus (PDA) on the RI of cerebral arteries in preterm infants from India. We intended to study the RI values in the cerebral arteries of preterm infants born throughout the neonatal intensive care unit (NICU) stay and compare the RI in those with hemodynamically significant patent ductus arteriosus (HSPDA) with those with hemodynamically insignificant or no patent ductus arteriosus (HIS/non-PDA). Methods: This was a prospective observational longitudinal study. All the Preterm infants of <32 weeks of gestational age admitted to NICU were included in the study. Results: The total number of preterm infants included were 70. The mean RI values in the right internal carotid artery (ICA), left ICA, anterior cerebral artery, and basilar artery were significantly higher in HSPDA as compared to HIS/non-PDA ([0.85 ± 0.01 vs. 0.76 ± 0.01, 0.86 ± 0.01 vs. 0.77 ± 0.01, 0.84 ± 0.01 vs. 0.74 ± 0.02, 0.8250 ± 0.01618 vs. 0.7194 ± 0.02437 [P < 0.0001] respectively). For gestational age, the RI values generally decreased with increasing age, ranging from 0.85 in the right ICA at 26 weeks to 0.76 at 31 weeks. Intraventricular hemorrhage (IVH) was significantly more common in the HSPDA group, affecting 55.6% of patients, compared to 5.8% in the HISPDA/non-PDA group (P = 0.01). Conclusion: RI values differed depending on the insonated artery. RI was lower in cases without PDA or hemodynamically insignificant PDA than those with HSPDA. This difference was statistically significant in all intracerebral arteries. IVH was more common and more severe in those with HSPDA.